PENGARUH SUBTITUSI EKSTRAK KULIT BUAH NAGA TERHADAP SIFAT ORGANOLEPTIK DAN TOTAL FLAVONOID SORBET BUAH KESEMEK - Putri Aditri (2020)
Flavonoids are one of the antioxidant compunds that acts an antidiabetic. Persimmon fruits and peel of dragon fruits are food that containts flavonoid. The purpose of this study is to determine the effect of red dragon fruit peel extract substitution on total flavonoid, nutrition fact and organoleptic properties of persimmon sorbet. This research used a Completely Randomized Designed (CRD). Formulas are divided into 3 with each percentage level of red dragon fruit peel extract substitution by F1 (13,3%), F2 (26,6%) and F3 ( 40%). Organoleptic test analysis will be performed using the Kruskal Wallis test and continued with the Mann Whitney test. Flavonoid total test analysis will be performed using ANOVA test and continued with the Duncan test. The result of the nalysis based on organoleptic test of red dragon fruit peel extract substitution had a significant effect (p<0,05) on panelist preference for colour, taste and texture. Based on flavonoid content test of substitution red dragon fruit extract did not have significant effect (p>0,005) on the flavonoid content of the persimmon fruit sorbet. The selected formula is F2 with 26.6% substitution red dragon fruit having 2,42 mg/g content flavonoid